Backward Pass Dalam Critical Path Method (Cpm): Konsep, Mekanisme, Dan Penerapannya Dalam Penjadwalan Proyek - Sasi Karisma Lutfiah; Nazwa Aqila Zulfahdi; Alika Oktaviana Andini; Maya Aulia Ramadhani; Jekson Waluyo; Ria Aulia (CV. ITTC INDONESIA, 2026)
Project scheduling is one of the crucial aspects in project management that determines the success of completing work on time. This article is a conceptual study (literature review) that discusses in depth the Backward Pass method within the framework of the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT). Backward Pass is the process of calculating the Latest Start (LS) and Latest Finish (LF) of each project activity, starting from the last activity toward the first. Through a literature review from various sources, this article explains the basic concepts of PERT/CPM, the working mechanisms of Forward Pass and Backward Pass, how to determine the Critical Path, Slack Time calculation, and the preparation of Gantt Charts and workforce requirement tables. Accompanied by calculation examples, this article is expected to serve as a comprehensive reference for academics and practitioners in understanding and applying the Backward Pass method to various types of projects.